Santri Community, Charisma, and the Contrast Political Agency: Electoral Victory and Defeat in Jombang and Mojokerto, Indonesia - Agus Machfud Fauzi; Novi Fitia Maliha; Pambudi Handoyo; Eufrasia Kartika Hanindraputri; Suyatno Ladiqi (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2025)
The phenomenon of the santri community and the choice of regional head candidates in local politics in Indonesia displays heterogeneous dynamics across regions. In the 2024 regional elections, Gus Barra, son of KH. Asep Saifuddin Chalim won the contest in Mojokerto, while Bu Nyai Munjidah, daughter of the late KH. A. Wahab Chasbullah, lost in Jombang despite having a strong religious pedigree. Both had the capital to win their second terms as incumbents, but the final results differed. This study aims to explain why the charisma and branding of their parents as kiai produced different electoral outcomes in these two santri regions, thereby contradicting the general understanding that santri communities are homogeneous and contributing to the literature on local Islamic democracy and the sociology of religious politics in Southeast Asia. This article uses a comparative qualitative method, drawing on interviews with political elites and Islamic boarding school figures, local media analysis, and KPU data. Weberian charisma and political agency theories are used to interpret the role of santri communities as active actors in the local democratic process, negotiating political choices. The research results show that victory or defeat is not solely determined by religious capital as the primary factor, but is also influenced by gender factors, political patronage, political campaigns, branding, and fragmented support from Islamic boarding schools. In conclusion, the santri community possesses dynamic, context-specific political agency that cannot be equated across regions.